ANALISIS PERBANDINGAN METODE BIAYA TRADISIONAL DAN METODE ACTIVITY BASED COSTING DALAM PERHITUNGAN HARGA POKOK PRODUKSI PERUSAHAAN KONVEKSI FIRMAN - Hidayat, Rahmat; Wati, Delvia; Ardila, Novrisa; Tachta Hinggo S, Hichmaed (Research in Accounting Journal (RAJ), 2021)
Increased business competition in various fields is the basis of this research. Good cost control will provide effectiveness and efficiency in spending costs so that optimal profits can be obtained in the midst of increasing business competition. The research method is a descriptive analysis method. Data collection is done through interviews, library research, documentation, and internet searching. The results showed that the Word convection company was not suitable to use the activity based costing method because it showed a higher value than the traditional cost method with a difference in value of Rp 1,503,509.